Negative regulation of hypoxia-inducible genes by the von Hippel-Lindau protein. - Iliopoulos, O (1996)
Inactivation of the von Hippel-Lindau protein (pVHL) has been implicated in the pathogenesis of renal carcinomas and central nervous system hemangioblastomas. These are highly vascular tumors which overproduce angiogenic peptides such as vascular endothelial growth factor/vascular permeability factor (VEGF/VPF). Renal carcinoma cells lacking wild-type pVHL were found to produce mRNAs encoding VEGF/VPF, the glucose transporter GLUT1, and the platelet-derived growth factor B chain under both normoxic and hypoxic conditions. Reintroduction of wild-type, but not mutant, pVHL into these cells specifically inhibited the production of these mRNAs under normoxic conditions, thus restoring their previously described hypoxia-inducible profile. Thus, pVHL appears to play a critical role in the transduction of signals generated by changes in ambient oxygen tension.